Review of Antibiotic Dosing with Peritonitis in APD. Issue 4 (July 2019) - Mancini, Ann; Piraino, Beth
Peritonitis is the leading cause of transfer from peritoneal dialysis (PD) to hemodialysis (HD). It is also the leading cause of hospitalization of PD patients. The usual treatment of peritonitis for automated PD (APD) patients consists of antibiotics given once daily in the long dwell. However, the once-daily antibiotic dosing recommendations are based primarily on studies with continuous ambulatory PD (CAPD) regimens. Published studies on antibiotic dosing in APD are very limited. We will review the scant literature on this topic. It is possible that extrapolating once-daily dosing from CAPD to APD may lead to underdosing. There is a need for further pharmacokinetic studies of antibiotic dosing in APD.